ACTUALIZATION OF QURAN VALUES ON RELIGIOUS MODERATION IN BANUROJA VILLAGE, GORONTALO, INDONESIA - Asfar, Khaerul; Hanif, Ni'matul; Daud, Ilyas; ., Mustaqimah; Khadhary, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
As a plural and multicultural country, Indonesia faces significant challenges in achieving harmony and national unity. A society made up of diverse ethnicities, cultures, and religions generally leads to complex issues. In fact, conflicts often revolve around the construction of places of worship, leadership transitions, and other matters. Banuroja Village is a community with diverse ethnic, cultural, and religious backgrounds, yet its people manage to live harmoniously. This research aims to explore the factors that enable the people of Banuroja Village to live harmoniously. It employs a qualitative approach to describe and analyze the social behaviors of the community through the sociological approach of the Quran. The data collection was conducted through interviews, observations, and documentation. The findings of this study indicate that the Banuroja community effectively actualizes Quranic values of religious moderation. The community has actualized the value of tawassut (moderation) and I'tidal (justice) as well as fostered balanced attitudes toward diversity, as reflected in peaceful and equitable leadership transitions. The embodiment of tasâmuh (tolerance) is seen from the absence of conflicts during the construction of worship houses because of respecting diversity. Furthermore, the emphasis on Shûrâ (consultative decision-making) has reinforced social solidarity within the community. Additionally, the commitment to al-La'unf (non-violence) and I'tirâf al-‘Urf (recognition of local customs) has fostered the development of a peaceful and harmonious social order. The actualization of these Quranic values positions Banuroja Village as a model of successful religious moderation, showcasing a community life free from inter-religious conflict.",